2022
DOI: 10.3389/fpsyg.2022.865306
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Adolescent Resilience on Mobile Phone Addiction During COVID-19 Normalization and Flooding in China: A Chain Mediating

Abstract: Natural disasters cause long-term psychological problems and increase substance use in some adults. However, it is unclear whether disasters also lead to these problems in adolescents. We hypothesized the influence of adolescent resilience on mobile phone addiction during the normalization of COVID-19 and flooding. We tested the mediating role of coping style and depression, anxiety, and stress (DASS) on phone addiction among 1,751 adolescents in the Henan Province in China. The adolescents were surveyed via a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…A meta-analysis has directly suggested that there is a moderate positive correlation between negative coping and problematic smartphone use among Chinese adolescents (Lu et al, 2021). Further support for this association has been furnished by cross-sectional studies involving diverse cohorts of adolescents hailing from various regions of China (Ma et al, 2022). A longitudinal study has also reported that maladaptive coping strategies are effective predictors of problematic smartphone use (He et al, 2020).…”
Section: The Possible Mediating Role Of Maladaptive Copingmentioning
confidence: 99%
“…A meta-analysis has directly suggested that there is a moderate positive correlation between negative coping and problematic smartphone use among Chinese adolescents (Lu et al, 2021). Further support for this association has been furnished by cross-sectional studies involving diverse cohorts of adolescents hailing from various regions of China (Ma et al, 2022). A longitudinal study has also reported that maladaptive coping strategies are effective predictors of problematic smartphone use (He et al, 2020).…”
Section: The Possible Mediating Role Of Maladaptive Copingmentioning
confidence: 99%
“…Internet-based addictive behaviors have intensified throughout the COVID-19 lockdowns ( Drouin et al, 2020 ; Huixi et al, 2020 ; Liu et al, 2021 ; Masaeli and Farhadi, 2021 ; Nan and Guangyu, 2021 ; Lai et al, 2022 ; Ma et al, 2022 ; Peng et al, 2022 ; de Freitas et al, 2022b ), leading to stress, anxiety, and depression. Smartphone addiction is related to stress and to unsatisfactory sleep patterns.…”
Section: Stress Anxiety and Depression Associated With Smartphone Ove...mentioning
confidence: 99%
“…When experiencing stress, resilience acts as a protective factor and reduces psychological distress [ 42 ]. Resilience is significantly and negatively associated with substance abuse and behavioral disorders [ 43 ]. However, the relationship between resilience and nomophobia remains unclear.…”
Section: Introductionmentioning
confidence: 99%